Utilizing nanomagnetic materials to eliminate Pb+2 and Cd+2 from aqueous mixtures - Zahra Al-Timimi; Zeina J. Tammemi (Current Research in Green and Sustainable Chemistry, 2022)
The magnetic structure of NiFe2O4 particles has been obtained by using a sol-gel auto combustion technique with limejuice as a surface-active agent as well as a fuel agent. The above process is classified as sustainable chemistry, which is a procedure that is both environmentally friendly and less expensive than other methods. Some of the physical and chemical techniques used to diagnose nanomaterials include energy-dispersive X-ray spectroscopy, XRD, FTIR, TEM, FESEM, and Brunauer-Emmett-Teller. The phase purity and particle size of 24.27 ​nm were revealed by XRD patterns. Pb+2, as well as Cd+2 absorption characteristics, have been investigated in relation to adsorbent concentration, pH, temperature, and contact time. When the pH ranges from three to nine, the best time to contact is 60 ​min for Pb+2 and 90 ​min for Cd+2. When compared to the Langmuir adsorption model, the adsorption studies revealed a strong relationship with a Freundlich adsorption isotherm. The thermophysical properties have been described, showing an endothermic reaction for ΔH, a spontaneous process for ΔG, as well as a positive value for ΔS, which was characterized by an increase in process disorder.